A Review On Panchnidan Of Ekakushtha w.s.r. To Psoriasis - Patidar, Anika; Sasmal, Sipra; Masodkar, Pankaj; Adhikar, S K Das (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurveda all skin disease have been described under the umbrella of Kustha . The objective of this article is to analyze Ekkustha, its etiology , etiopathogenesis, management from different ayurvedic Literature . Kushtha is divided into two types Mahakushtha and Kshudrakushtha.Mahakushtha again divided in to seven types and Kshudrakushtha into eleven types. Out of eleven types Ekkustha is of them. Though Ekakushtha is included under kushta , hence etiology , etiopathogenesis, and management are same. ‘Sapta dravya’ i.e Three dosha and Tvak, Rakta, Mamsa, Lasika plays an important role in etiopathogenesis of Kushtha as well as Ekakushtha having predominance Vata Kapha Dosha . Psoriasis is a chronic, non infectious, inflammatory dermatosis characterized by well demarcated erythmatous plaques topped by silvery scale . Similar to Swedana, Mahavastu and Matsyashakalopam avastha of Ekakushtha . Management like Shodhana therapy at regular interval, Shaman therapy, Local application with different lepa, oil and all these aspects have been described here according to different acharya